Local recurrence after endoscopic resection of sessile serrated lesions: A multicenter prospective study by the Osaka Gut Forum. Issue 12 (1st November 2022) - Shichijo, Satoki; Yamaguchi, Shinjiro; Nakamatsu, Dai; Inoue, Takanori; Nakahara, Masanori; Ogiyama, Hideharu; Yamada, Takuya; Kinoshita, Kazuro; Ishihara, Ryu; Michida, Tomoki; Nishida, Tsutomu; Tsujii, Yoshiki; et al.
Abstract: Background and Aim: Sessile serrated lesions (SSLs) act as precursors to colorectal cancer, sometimes harbor carcinomas, and are sometimes incompletely resected. We aimed to evaluate local recurrence after endoscopic resection of SSL ≥10 mm. Methods: This prospective, single‐arm, observational study was performed at eight Japanese tertiary institutions. Colorectal lesions ≥10 mm were resected endoscopically, and the pathological diagnosis was either an SSL or hyperplastic polyp (HP). Follow‐up colonoscopy was performed 1 year later, and the local recurrence was evaluated by biopsy. Results: From October 2018 to September 2021, 104 cases with 123 lesions were registered. Among the pathologically diagnosed 105 SSLs and 18 HPs, 95 and 7 lesions were diagnosed as SSLs and HPs, respectively, by central pathological review. Among the 104 endoscopically diagnosed SSLs, 86 were diagnosed as SSLs, whereas among the 11 endoscopically diagnosed HPs, two were diagnosed as HPs by central pathological review (the rest were SSLs). Among the 95 patients with 113 lesions who underwent follow‐up colonoscopy, resection scars were identified in 95 (84%) lesions. Three (3.1%; 95% confidence interval 0.6–8.7%) local recurrences were diagnosed pathologically among 98 pathologically diagnosed SSLs. Two (6%) local recurrences were diagnosed in patients with SSLs ≥20 mm. Conclusions: The local recurrence rate after endoscopic resection of SSLs ≥10 mm was 3.1%. Careful follow‐up is recommended after endoscopic resection of large SSLs. Endoscopically diagnosed HPs ≥10 mm were sometimes pathologically diagnosed as SSL and should be considered for resection.